2030 is tomorrow: transformative change for a mistreated mother Earth. Issue 3 (21st September 2020) - Richardson, Jacques G.; Erdelen, Walter R.
Abstract : Purpose: This study aims to assess progress toward achieving international (United Nations') goals and targets for attaining sustainable development and discuss the risks of worldwide failure. Design/methodology/approach: The authors highlight the relationship between global goals/targets and governance, relate this to the concept of sustainable development, outline and compare Millennium Development Goals and their successors, the Sustainable Development Goals (SDGs), and lastly view SDG implementation from two major spaces i.e. the governance and science space, respectively. Findings: Governance and culture as new components of sustainable development may be sine qua non for humanity's transformative action toward global and just sustainable development. Through fostering informed decision and policymaking, modern science, as sketched in this contribution, should provide the framework for realizing Agenda 2030. Earth System Science and its innovative notions such as the Anthropocene, planetary boundaries, tipping points and tipping elements will be key in the process of "designing" blank a sustainable future of and for Homo sapiens . Originality/value: This essay proposes developing holistic approaches to cooperate at all levels in urgent efforts to meet goals projected for 2030 and 2050. The complexity and functioning of the governance space, comprising a system of governance systems, is illustrated not only in the diversity of the institutional landscape but in particular through the blurring of all scales – local to global.